Problemy spójności społecznej i ekonomicznej w polityce energetycznej Unii Europejskiej - Fiedor, Bogusław (Problems of Social and Economic Cohesion in Energy Policy of the European Union, 2006)
The paper is an attempt to identify social and economic cohesion related components in EU energy policy. It starts with the analysis of social and economic cohesion issues against the background of primary law acts (founding treaties) as establishing the foundations of common energy policy, with special attention being paid to the Single European Act, Treaty of the European Union and Treaty of Amsterdam. Following that, the issues under consideration have been highlighted in the context of historical phases of development of common energy policy. The main part of the paper is devoted to social and economic cohesion issues from the point of view of energy markets liberalization which is the most important area of that policy. Within this part, there have been also included specific problems related to the Lisbon Strategy and a new framework energy policy of the EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 93-105